Modeling and optimization of photocatalytic treatment of pre-treated palm oil mill effluent (POME) in a UV/TiO2 system using response surface methodology (RSM). Issue 1 (1st January 2017) - Haji Alhaji, Mohammed; Sanaullah, Khairuddin; Fong Lim, Soh; Ragai Henry Rigit, Andrew; Hamza, Abdulhamid; Khan, Afrasyab
Abstract: This study aimed at the degradation of COD, BOD and Color present in palm oil mill effluent (POME) using UV/TiO2 system. A Statistical tool called face-centered central composite design has been run through response surface methodology by the use of design expert software to model and optimize the photodegradation process. The SEM average size of the synthesized TiO2 particle is 100 nm and this confirm that it is anatase. The prominent peak as reveal by XRD occur at 22.3° and this indicates that TiO2 formed is anatase. The FTIR results shows a peak value of 1, 406.50 and 1, 452.50 cm −1 indicating that the TiO2 anatase is formed while nonappearance of the peak at 2, 900 cm −1 indicates that the all organic compounds have been removed after calcination. The three models developed for the three pollutants are non-significant as revealed from the Prob > F values of 0.0584 for COD, 0.0612 for BOD and 0.4239 for color and this confirms that proposed models fit the experimental data. The optimum conditions for the three parameters are 5.50 for initial pH, 4.84 mg for catalyst dosage and 42.86 min for time and the percentage removal of the COD, BOD, and color are within the range of 59.43–96.81%, 48.05–102.68% and 60.63–94.29% respectively. Regression analysis obtained through analysis of variance provided significant quadratic polynomial with the coefficient of determination R 2 = 0.9646, 0.9496 and 0.9223 for COD, BOD, and Color removal respectively.